Non-templated ambient nanoperforation of graphene: a novel scalable process and its exploitation for energy and environmental applications - Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (Nanoscale, 2015)
Nano-perforation of 2D graphene sheets is a recent and strategically significant means to exploit such materials in modern applications such as energy production and storage. However, current options for the synthesis of holey graphene (hG) through nano-perforation of graphene involve industrially undesirable steps viz., usage of expensive/noble metal or silica nanoparticle templates and/or hazardous chemicals. This severely hampers its scope for large scale production and further exploitation. Herein, we report for the first time a scalable non-templated route to produce hG at ambient conditions. Nano-perforation is achieved with tunable pore size via the simple few layer co-assembly of silicate-surfactant admicelles along the surface of graphene oxide. A gentle alkali treatment and a reduction at optimized conditions readily yielded holey graphene with a remarkable capacitance (similar to 250 F g(-1)) and interesting adsorption abilities for pollutants. Density functional theory based computational studies reveal interesting insights on the template free nano-perforation at a molecular level. This simple rapid process not only excludes the need for expensive templates and harmful chemicals to yield hG at attractively ambient, chemically placid and industrially safer conditions, but also creates no hurdles in terms of scaling up.